Surface modification of polycarbonate films with 2-hydroxyethylmethacrylate (HEMA) and N-vinyl pyrrolidone (NVP) monomers by radiation techniques - Manjira Chowdhury; Pinku Poddar; A.S.M. Kashem; Md. Sahadat Hossain; Kazi Imtiaz Ahmed Nakib; M.A. Khan; A. M. Sarwaruddin Chowdhury (Results in Engineering, 2024)
In order to modify the surface as well as mechanical properties, polycarbonate (PC) films were grafted with two types of monomers such as 2-hydroxyethylmethacrylate (HEMA) & N-vinyl pyrrolidone (NVP). Material preparation is carried out by a periodic orientation of monomer solutions having methanol of dissimilar concentration in addition with photo-initiator [Irgacure 907]. Polycarbonate (PC) films were cut into dumbbell shape (10 × 3) mm [ASTM], impregnated into the devised solutions and irradiated under both ultraviolet (UV) and Co-60 gamma radiation. Extent of polymer loading (PL) (%) was calculated in order to assess the amount of grafted polycarbonate (PC-g-HEMA) formed under certain conditions of the experiment. Various property parameters such as elongation at break, tensile strength, modulus, absorption of water, gel content etc. were studied. 30% HEMA and 120-min irradiation time showed the better grafting with respect to the qualities studied. Water absorption was found much low by the treated (PC-g-HEMA) samples with compared to the untreated samples. The loss of mechanical property in grafted polycarbonate due to UV aging and simulating weathering degradation was found higher in untreated polycarbonate than that of grafted one. Effect of monomer N-vinyl pyrrolidone (NVP) on to PC films under UV radiation was also examined and various mechanical properties (tensile strength, polymer loading, elongation at break and tensile modulus) were studied. 20% NVP with the duration of 240 min irradiation time showed the maximum mechanical properties. The sample was found to destroy up to the concentration of 20% NVP.